2018
DOI: 10.5812/ijcm.83370
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acetylcholinesterase, Paraxonase, and Oxidative Stress in Breast Tumors

Abstract: Background: Oxidative stress is associated with the development of a large variety of malignancies. Objectives: This study was conducted to evaluate the acetylcholinesterase (AChE) and arylesterase (ARE) activities, malondialdehyde (MDA), and total antioxidant capacity (TAC) plasma levels in two groups of patient with breast cancer and benign breast diseases compared to healthy volunteers. Methods: The present study was composed of two groups of patients with malignant breast tumors (MBT) and benign breast dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…In addition, the results manifested that the TAC levels and AChE activity were higher in the PTC group compared to the BTN group, indicating that the levels of OS were higher in the PTC group compared to the BTN group. It can be concluded that the OS levels depend on the type of pesticides as well as the amount and period of exposure, as reported previously (9)(10)(11)32).…”
supporting
confidence: 84%
See 2 more Smart Citations
“…In addition, the results manifested that the TAC levels and AChE activity were higher in the PTC group compared to the BTN group, indicating that the levels of OS were higher in the PTC group compared to the BTN group. It can be concluded that the OS levels depend on the type of pesticides as well as the amount and period of exposure, as reported previously (9)(10)(11)32).…”
supporting
confidence: 84%
“…OCPs disrupt human metabolism by increasing oxidative stress (OS) levels (9)(10)(11)(12). The loss of balance between the formation of reactive oxygen species (ROS) or nitrogen species (RNS) such as nitric oxide (NO) and the antioxidant defense mechanisms leads to a phenomenon called oxidative stress (OS) (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of any balance between ROS synthesis and antioxidants is referred to as oxidative stress 7 . Inflammatory factors such as NF‐κβ and its associated genes, namely, inducible nitric oxide synthase (iNOS) and COX‐2, can be triggered by oxidative stress, which results in the aging process caused by the pervasive inflammation‐related responses 8 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Lack of any balance between ROS synthesis and antioxidants is referred to as oxidative stress. 7 Inflammatory factors such as NF-κβ and its associated genes, namely, inducible nitric oxide synthase (iNOS) and COX-2, can be triggered by oxidative stress, which results in the aging process caused by the pervasive inflammation-related responses. 8 By scavenging free radicals such as hydroxyl radicals and superoxide anions, antioxidants can reduce the degree of damage caused by ROS, thus helping to prevent organisms' aging.…”
Section: Introductionmentioning
confidence: 99%